2008
DOI: 10.1109/icpr.2008.4761358
|View full text |Cite
|
Sign up to set email alerts
|

An adjustable combination of linear regression and modified probabilistic neural network for anti-spam filtering

Abstract: Email is a commonly used tool for communication which allows rapid and asynchronous communication.The growing popularity and low cost of e-mails have made spamming an extremely serious problem today. Several anti-spam filtering techniques have been developed but most of them suffer from low accuracy and high false alarm rate due to complexity and changing nature of unsolicited messages. This study proposes an innovative classification framework with comparable accuracy, affordable computation and high system r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…A MCS architecture also allows to easily add new classifiers or detection modules to an existing system, which is a common practice in network intrusion detection and spam filtering tasks to counteract new kinds of attacks. Recently, it has also been argued that MCSs allow to improve classifier robustness in several adversarial classification tasks, based on the intuitive motivation that an adversary has to evade more than one classifier to make the whole ensemble ineffective [29,44,46,47,52]. However, this claim has not been supported by any clear theoretical or empirical evidence so far.…”
Section: Mcss In Adversarial Classification Tasksmentioning
confidence: 94%
See 1 more Smart Citation
“…A MCS architecture also allows to easily add new classifiers or detection modules to an existing system, which is a common practice in network intrusion detection and spam filtering tasks to counteract new kinds of attacks. Recently, it has also been argued that MCSs allow to improve classifier robustness in several adversarial classification tasks, based on the intuitive motivation that an adversary has to evade more than one classifier to make the whole ensemble ineffective [29,44,46,47,52]. However, this claim has not been supported by any clear theoretical or empirical evidence so far.…”
Section: Mcss In Adversarial Classification Tasksmentioning
confidence: 94%
“…During the past fifteen years MCSs became a state-of-the-art tool for the design of pattern classifiers, mainly because of their capability to improve accuracy with respect to an individual classifier. Some authors have recently argued that MCSs can also improve robustness in adversarial settings, since in principle more than one classifier has to be evaded to make the whole ensemble ineffective [29,44,46,52]. However, this claim has never been investigated in depth, and remains questionable.…”
mentioning
confidence: 97%
“…We finally deploy our learning algorithm within a traditional random forest framework (Breiman 2001) and show its predictive power on real-world datasets. Notice that, although there have been various proposals that tried to improve robustness against evasion attacks by using ensemble methods (Hershkop and Stolfo 2005;Perdisci et al 2006;Tran et al 2008;Biggio et al 2010), it was shown that ensembles of weak models are not necessarily strong (He et al 2017). We avoid this shortcoming by employing Treant to train an ensemble of decision trees which are individually resilient to evasion attempts.…”
Section: Introductionmentioning
confidence: 99%
“…MCSs are currently being used in several adversarial classification tasks, like multimodal biometric systems [1,4], intrusion detection in computer systems [2], and spam filtering [11][12][13]. Two practical reasons are that in many of such tasks several heterogeneous feature subsets are available, and they can be easily exploited in a MCS architecture where each individual classifier is trained on a different feature subset [1]; moreover, in tasks like intrusion detection it is often necessary to face never-seen-before attacks, which can be easily done with a MCS architecture by adding new classifiers.…”
Section: Related Workmentioning
confidence: 99%